Pengaruh Pengurangan Kebisingan terhadap Produktivitas Telur Itik Alabio - Meri Rahmi; Dadan Heryada Wigenaputra; Ade Ramdan; Widya Prapti Pratiwi; Sidik Permana (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service aims to determine the effect of noise levels on the growth, development, and behavior of Alabio ducks, for a population of 400 (16 males and 384 females). The noise level of the diesel engine was 94.3 dB, and at a distance of about 5 meters from the sound source, the behavioral ducks were changed such as running from the farm area, decreased eating patterns, stunted growth, and reduced egg production. After replacing the diesel engine with a motor engine that did not produce noise (0 dB), there was a significant change in the condition of the ducks. Noise level testing used the Sound Meter Level application with a measuring distance of 1-12 meters from the alabio duck cage. The rice pounding machine and rice smoother with driving power have been modified with a diesel motor turned on simultaneously. The sound produced was measured every 1 meter for 30 seconds. The noise level produced was an average of 70.5 dB. The noise level produced has been significantly reduced, so with this condition, the behavior of the ducks began to change. The ducks no longer leave the farm area (pens and ponds), and the eating pattern increased significantly due to the loss of stress factors due to noise, which has a positive impact on growth acceleration. This program is expected to increase the productivity of eggs produced by ducks. This service shows that reducing noise levels has a positive effect on the welfare, growth, and productivity of Alabio ducks.